Implementasi Pemasaran Digital Menggunakan ShopeeFood untuk Meningkatkan Penjualan (Studi Kasus Rumah Es Nina) - Afandi, Khoirunnisa; Arief, M. Habibullah; Ranggianto, Narandha Arya; Fadhil, Martiana Kholila (Abdimas Indonesian Journal, 2024)
The current digital marketing trend is experiencing significant transformation. Micro and Small and Medium Enterprises (MSMEs) need a marketing strategy for a product using a digital platform to increase business excellence and optimize business to reach a broader range of consumers. This community service aims to evaluate MSMEs such as Nina's Ice House in Jember Regency in optimizing the use of ShopeeFood as a marketing platform. The method used in this community service activity is qualitative descriptive analysis. The service activity scheme goes through needs analysis, implementation, and evaluation. This digital marketing empowerment was done by interviewing and training on the ShopeeFood application with MSME sellers of Nina's Ice House in Jember Regency. The expected results of this service are increased knowledge ownership, sales, and visibility of Nina's Ice House products. This service supports business sustainability and provides insight for other MSME players in utilizing digital marketing to strengthen competitiveness.